Analysis Of Teacher Performance In The Learning Process At MTs Alif Laam Miim Surabaya - Husaini, Muhammad; Arifin, Shokhibul; Puspita Sari, Ika (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine teacher performance based on the abilities possessed by teachers. The benefit of this research is that it can enrich the body of knowledge, especially about teacher performance in terms of ability, to improve the quality of learning. In addition, this research is also useful as a reference for teacher performance in various aspects, especially in teaching and learning activities. This study uses a qualitative descriptive method by conducting an in-depth study to obtain complete and accurate data. It uses a qualitative approach to describe and interpret objects or facts as they are. The results showed that the average teacher at MTS Alif Laam Miim Surabaya performed quite well in terms of their level of competence. It can be seen from the implementation of activities and the achievement of learning activities.